2017
DOI: 10.1177/0951484817745695
|View full text |Cite
|
Sign up to set email alerts
|

Critical success factors in implementing an e-rostering system in a healthcare organisation

Abstract: Effective and efficient staff scheduling has always been a challenging issue, especially in health service organisations. Both the extremes of staff shortage and overage have an adverse impact on the performance of healthcare organisations. In this case, an electronic and systematic staff scheduling (e-rostering) system is the often seen as the best solution. Unless an organisation has an effective implementation of such a system, possible cost savings, efficiency, and benefits could be minimal. This study is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 23 publications
0
7
0
1
Order By: Relevance
“…Questionnaires were used in most studies ( n = 13). Two studies collected data from the shift scheduling program Titania Consultants to Government and Industry (Karhula et al., 2020; Turunen et al., 2020), one study used a national database of nursing quality indicators (Wright et al., 2017), one study used a case study and interviews (Silvestro & Silvestro, 2000) and data from one study were collected using semi‐structured interviews and observations (Soomro et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Questionnaires were used in most studies ( n = 13). Two studies collected data from the shift scheduling program Titania Consultants to Government and Industry (Karhula et al., 2020; Turunen et al., 2020), one study used a national database of nursing quality indicators (Wright et al., 2017), one study used a case study and interviews (Silvestro & Silvestro, 2000) and data from one study were collected using semi‐structured interviews and observations (Soomro et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The level of overtime dropped considerably in the fixed scheduling wards and was lower during the 8 months of the study in comparison to self-scheduling wards where overtime remained unchanged. Soomro et al (2018) found that the critical success factors for implementing an e-Rostering system included motivational factors such as evidence of the advantages of the system, technical support, an effective policy, committed leadership, clear aims and objectives, senior management support, monitoring, reporting and effective communication.…”
Section: Healthcare and Roster Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The literature highlights certain adverse outcomes associated with the electronic scheduling process, such as the relationship between the lead nurse and her coworkers [31]. Also, implementing electronic scheduling software should be gradual, and not sudden, as Soomro et al [32] suggest, otherwise there is likely to be more staff illness and consequential absence [33]. The factors for successfully implementing an e-rostering system in healthcare organization include proper policy and compliance in system implementation, technical support, proper leadership, sound goals and objectives, gradual implementation, evidence of the advantages offered by the new system, support from upper (senior) management and strong communication between all levels of staff.…”
Section: Discussionmentioning
confidence: 99%
“…Прочная коммуникационная связь между всеми уровнями иерархической системы выступает одним из основных факторов успеха для преодоления психологического дискомфорта, связанного с переменами в рабочем процессе. Именно коллегиальное сотрудничество с определением круга ответственных за отчетность лиц позволит обеспечить эффективный мониторинг внедрения [27].…”
Section: разработка технологии и планирование ее внедренияunclassified